The nature of social support provided by primary caregivers to cancer-diagnosed patients. - Garagan, Fleur V.
This study focused on the exchanges of social support between primary caregivers and cancer diagnosed patients. It wanted to know the nature of social support provided by primary caregivers to cancer-diagnosed patients. Specifically, it aimed to describe the primary caregivers and patients by their primary caregiver. The study described the nature of support given to the patient by their primary caregiver. The study described the nature of support in terms of the caregiver and patient's socio-economic characteristics. Lastly, it aimed to know how other sources of support extended assistance to the patient and to the primary caregiver.